Model Komunikasi AISAS Sebagai Efektifitas Paid Promote Terhadap Keputusan Pembelian Konsumen - Danang Satrio; Ari Muhardono; Dini Hari Mentariku Lahir (Jurnal Ekonomika dan Bisnis, 2023)
This study aims to test and analyze the influence of the AISAS communication model as the effectiveness of paid promote on consumers' purchasing decisions. The free variables in this study are Attention, Interest, Search, Action and Share. The population in the study were Instagram users who followed Instagram accounts @giladiskonn aged 17-45th, and took a sample of 121 people. The analytical tool used in this study is linear regression analysis using SPSS software. Based on the results of hypothesis testing, it is known that the Attention and Share variables have a significant effect on consumers' purchasing decisions, while the Interest, Search and Action variables do not have a significant effect on consumers' purchasing decisions.